MANAJEMEN MEDIA MASSA NUSA BALI PASCA KEBIJAKAN KONVERGENSI - Putri Pramesti, Luh Komang; Alit Suryawati, I Gusti Agung; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT The development of the internet media being an alternative that more interested than cast media. The alternation of consume system and access media make industrial organizer to reorganize the position which make it still relevant to their consumer. The direct effect of the changes in media consumption is a reduction in the number of circulations news paper, This pattern is filled by one of Balinese news paper is NusaBali. Finally NusaBali media choosed to change their management after convergencetion policy for increasing company’s credibility in media competition. Based on the concept of Management Mass Media Companies (6M), the researchers analyst how to the mass media management of NusaBali after convergence policy. In this research the researchers using descriptive cualitative method. The technique of accumulation by interviews and documentation. The result of the research showing after convergence policy, NusaBali have two management, there are NusaBali management and NusaBali.com management. .   Keywords: Management Mass Media, Convergence, NusaBali Media